New species of Chimaera (Chondrichthyes: Holocephali: Chimaeriformes: Chimaeridae) from the Southwestern Indian Ocean - Clerkin, Paul J.; Ebert, David A.; Kemper, Jenny M. (Zootaxa, 2017)
Three new species of Chimaera are described from the Southwestern Indian Ocean. Chimaera willwatchi sp. nov. is distinguished by its large body, blocky head with square snout, well-defined suborbital ridges, and a strong dorsal spine exceeding first dorsal apex; body brown-purple in color, slight iridescent sheen, heavily mottled around mouth and ventral surface, posterior edge of pelvic fins and first dorsal fin with prominent white margin, and anterior edge of second dorsal fin with white margin. Chimaera didierae sp. nov. can be distinguished by its light tan body color, slender body, short trunk, long tail, relatively robust spine, very small unpaired fins, and extremely deciduous skin. Chimaera buccanigella sp. nov. is distinguished by its light tan body color, stocky body, short trunk, tapering rapidly into a long tail, long, very straight spine, skin not deciduous. The three Chimaera species were collected from seamounts of Walters Shoal, the Madagascar Ridge, and the Southwestern Indian Ridge in an area within 34o30’S–44o05’E and 39o30’S–58o15’E. This is the first record of the genus in the Southwestern Indian Ocean, and brings the global total to 19 species. The new species presented here are distinguishable from their congeners by a combination of coloration, morphology, meristic, and structure of the mitochondrial NADH2 gene.